BIAYA TRANSAKSI USAHA TANI SAPI POTONG DI KABUPATEN PAMEKASAN - Farahdilla kutsiyah (MADURANCH: Jurnal Ilmu Peternakan, 2011)
This article analyzed the transaction costs of the cattle’s farmers. Survey and direct field observation were conducted in Pamekasan Regency. Respondents determinition used cluster randomly sampling methods.Sampel size was taken 131 peasants. The collected data was analyzed discriptively and multiple linier regression test. The research showed that the increasing factor significantly are execution costs and the amount of using of transaction service. Meanwhile this execution costs are the major contribution to the total transaction cost